Study on Waste Heat-Driven Refrigeration System for Energy Saving and Fast Cooling of Dust Collector in Monocrystalline Silicon Manufacture - Hou, Jiwei; Xu, Yingjie (Frontiers in Energy Research, 2021)
Single-crystal silicon is key raw material in photovoltaic industry. In its manufacture, silicon monoxide dust, a byproduct, is collected under vacuum environment. To clean the dust collector, air is recharged into the collector, reacting with the dust and causing very high temperature. Collector components may be damaged. It also takes several hours to cool down. In this paper, a cooling system based on ejection refrigeration cycle is proposed, which collects the reaction heat and simultaneously controls the collector temperature around 100°C. Then, it is driven by stored waste reaction heat and cools down the dust to a lower temperature. The designed cooling system, employing a 9.7972 m2 fin-tube heat exchanger, can simultaneously meet the cooling load of four dust collectors with 330L/S capacity. By a thermodynamic model established in this work, performance analysis is carried out. Generating temperature around 73°C and evaporating temperature around 6°C are recommended for system operation. Results also show the cooling system is able to provide 3270 kJ cooling energy that is needed by the collector, for fast cooling down the dust no longer than 620 s. It is about 92% shorter than the time of current collector, indicating the cooling system is effective and feasible.